Comparisonal Analysis of Costs And Working Time Column Using Semi System Form and Aluminum Form in Building Project Case Study : Osaka Riverview Apartment Project - Aji Tri Setiadi; Elhazri Hasdian; Yopi Lutfiansyah; Novika Candra Fertilia (NAROTAMA UNIVERSITY, Indonesia, 2021)
In planning a building or infrastructure, various methods and strategies are needed to achieve the target for timely completion, resulting in a strong and beautiful quality building. Structural components such as foundations, columns, beams, and plates play an important role in supporting the establishment of a building. To produce the quality of the structural components required special skills in doing the job. Formwork has an important value as a mold (formwork) to form the dimensions of the structural components that have been planned. In this study, we will discuss the comparison of usage related to the cost and time of using different column formwork, namely semi-system formwork and aluminum formwork used to build multi-storey buildings. From the two types of formwork, the budget for formwork work will be analyzed to obtain an economical budget and efficient time. The comparative analysis of formwork semi system and formwork aluminum get results, for formwork semi system requires a cost of Rp. 1,366,460,000 with an implementation time of 35 days while using aluminum formwork is Rp. 1,114,460,000 with an implementation time of 20 days. This means that using semi system formwork is more expensive by Rp. 252,000,000 compared to semi system formwork. Meanwhile, the implementation time for aluminum formwork is 15 days faster than semi-system formwork.